2007
DOI: 10.1080/13607860600637810
|View full text |Cite
|
Sign up to set email alerts
|

The Care Home Activity Project: Does introducing an occupational therapy programme reduce depression in care homes?

Abstract: The primary aim of the study was to test the hypothesis that depression severity in care homes for older people would be reduced by an occupational therapy programme. This was a feasibility study for a cluster randomised controlled trial and involved four intervention and four control homes in northern England. In each intervention home a registered occupational therapist worked full-time for one year delivering an individualised programme to participants. Pre- and post-intervention data for the Geriatric Ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
0
19
0
2
Order By: Relevance
“…Mozley et al . () evaluated the effects of an occupational therapy programme on residents with depression. There was no significant difference found using quantitative outcomes between the groups who did and did not receive the programme, but there was qualitative evidence of benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Mozley et al . () evaluated the effects of an occupational therapy programme on residents with depression. There was no significant difference found using quantitative outcomes between the groups who did and did not receive the programme, but there was qualitative evidence of benefit.…”
Section: Introductionmentioning
confidence: 99%
“…This was higher than the original estimate of 15%, which was based on previous local studies. 63,131 The ICCs from the NPI and CMAI data were between 0.03 and 0.06 (except for the NPI distress subscale; see Table 25), and so were higher than the value of 0.03 used in the original sample size estimation. The dropout rate in the other residents group, consisting of residents with dementia or with CB but not both, was 17% and, therefore, closer to our original estimate of 15%.…”
Section: Dropoutsmentioning
confidence: 96%
“…Mozley et al, 131 in a study carried out in the same locality as the ResCare trial, reported a 39% loss of care home participants over 12 months because of death, moving elsewhere or illness too severe for follow-up. So we expected to lose two recruited CB residents (15%) per home over 4 months, yielding a completed sample of 48 × 11 = 528 participants.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…58 A previous study, assessing the feasibility of a trial evaluating the effectiveness of an OT programme at reducing levels of depression in a care home population, found no significant effects. 60 However, the trial was not powered to evaluate the efficacy of OT in alleviating in symptoms of depression. The OTCH trial sought to assess the influence of OT on levels of depression as a secondary outcome measure to the performance of personal ADL.…”
Section: Depression In Stroke Survivors Residing In Care Homesmentioning
confidence: 99%